(t-10)(t+11)=

Simple and best practice solution for (t-10)(t+11)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t-10)(t+11)= equation:


Simplifying
(t + -10)(t + 11) = 0

Reorder the terms:
(-10 + t)(t + 11) = 0

Reorder the terms:
(-10 + t)(11 + t) = 0

Multiply (-10 + t) * (11 + t)
(-10(11 + t) + t(11 + t)) = 0
((11 * -10 + t * -10) + t(11 + t)) = 0
((-110 + -10t) + t(11 + t)) = 0
(-110 + -10t + (11 * t + t * t)) = 0
(-110 + -10t + (11t + t2)) = 0

Combine like terms: -10t + 11t = 1t
(-110 + 1t + t2) = 0

Solving
-110 + 1t + t2 = 0

Solving for variable 't'.

Factor a trinomial.
(-11 + -1t)(10 + -1t) = 0

Subproblem 1

Set the factor '(-11 + -1t)' equal to zero and attempt to solve: Simplifying -11 + -1t = 0 Solving -11 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -1t = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -1t = 0 + 11 -1t = 0 + 11 Combine like terms: 0 + 11 = 11 -1t = 11 Divide each side by '-1'. t = -11 Simplifying t = -11

Subproblem 2

Set the factor '(10 + -1t)' equal to zero and attempt to solve: Simplifying 10 + -1t = 0 Solving 10 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1t = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1t = 0 + -10 -1t = 0 + -10 Combine like terms: 0 + -10 = -10 -1t = -10 Divide each side by '-1'. t = 10 Simplifying t = 10

Solution

t = {-11, 10}

See similar equations:

| p=s/14 | | x^3-20x^2+64x=0 | | 8/9z-1/2=-2/3z+1/6 | | 300+2x-125-7x=75 | | 1/3(1/2-1/3)-1/3(1/3-1/2) | | u-v=18 | | 3/5x+5=14 | | 2n^2-2n=7 | | 3-(x+1)=2-(x+6) | | w-6=8 | | 3(-4x-4)-5=16 | | 2(n-6)-(9+3n)=-2n | | 6+8(4w+3)= | | v/15=u | | x/y=1/2 | | 3c+c=24 | | 3x+18=23-2x | | -15+-13= | | 10-(2y-2)=1-3y | | 10=m+n | | 0.4x+3=0.7x-3 | | 10x=42-4x | | y-18=x | | 9x=22-2x | | 3(x+2)=13 | | 4/3=12/x-3 | | 12=b/a | | 25x^2-144b^2=0 | | p=s+20 | | 9x+8x=x | | 20=4r+8 | | -(3x+6)=5-(2-x) |

Equations solver categories